Mitigating climate change : the emerging face of modern cities - Khare, Anshuman ; Beckman, Terry (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013., 2017)
XXII, 281 p. 66 illus., 46 illus. in color. digital.